PENERAPAN PENGENDALIAN KUALITAS JENIS VARIABEL PADA PRODUKSI MAKANAN (Studi Kasus pada Pabrik Wingko Babat Cap “Moel” Semarang) - Dewiga, Pramestiara; Sudarno, Sudarno; Prahutama, Alan (Jurnal Gaussian, 2015)
Wingko is a typical product from Semarang that growing and evolving because of the increase in tourism of Semarang City. Competition between each producer requires them to improve product quality. This study aims to minimize defective products and to monitor the distribution of the product to be worthy. Factors that are used as the benchmarks a wingko production process are the net weight and oven temperature for acceptance sampling plan. The R,  dan s control charts are used to monitor the production process and estimated capability process is used to minimize process defects. While acceptance sampling plans are used to determine the feasible product to distribute or not. Based on the analyze result that the production process is controlled after eliminating the 1st and the 28th sample number. Estimated capability process of 1.2508 indicates that it is a little defect product produced and DPMO value of 180 means that there are 180 defects per one million productions. While the acceptance sampling plan according to single specification limit either form 1 and form 2 indicates that wingko was acceptable (can be distributed). Keywords: Wingko, Net Weight, Quality Control, Capability Process